Pengaruh Keragaman Produk Dan Lokasi Penjualan Terhadap Kepuasan Konsumen Pada Duta Grosir Kota Bima - Nur Ayu; Ismunandar Ismunandar; Nur Khusnul Hamidah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Consumer satisfaction is the extent to which an individual is pleased with a product or service overall after obtaining and using it. If the value is far below their expectations, they will feel upset. The purpose of this study was to determine the effect of product diversity and sales location on consumer satisfaction at Duta Grosir Kota Bima. This study is an associative type using a Likert scale questionnaire as an instrument. The population of this study was all consumers who had purchased products at Duta Raja Grosir Kota Bima whose exact number was unknown with a sample size of 96 people using the purposive sampling method. data were collected by means of observation, questionnaires and literature studies. Data analysis was carried out by validity test, reliability test, classical assumption test, multiple linear regression, multiple correlation coefficient, determination test, t test and f test. The results showed that product diversity and sales location had a significant effect on consumer satisfaction at Duta Grosir Kota Bima